2017
DOI: 10.1016/j.jand.2017.04.002
|View full text |Cite|
|
Sign up to set email alerts
|

Is Nutrient Content and Other Label Information for Prescription Prenatal Supplements Different from Nonprescription Products?

Abstract: Background Prenatal supplements are often recommended to pregnant women to help meet their nutrient needs. Many products are available making it difficult to choose a suitable supplement, as little is known about their labeling and contents to evaluate their appropriateness. Objective To determine differences between prescription and nonprescription prenatal supplements available in the US regarding declared nutrient and non-nutrient ingredients, and the presence of dosing and safety-related information. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Our study found that 73.9% of women taking a supplement containing iodine were taking a product with at least 150 µg per serving (data not shown). Saldanha et al found that for dietary supplements that were specifically marketed as prenatal supplements, the mean iodine content of prescription prenatal supplements was 150 ± 4.8 µg and for non-prescription prenatal supplements, it was 164 ± 6.7 ug [ 26 ]. As it is unlikely there has been a dramatic reduction in the amount of iodine included in dietary supplements containing at least some iodine, the lower median may be due to women reporting less frequent use of supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that 73.9% of women taking a supplement containing iodine were taking a product with at least 150 µg per serving (data not shown). Saldanha et al found that for dietary supplements that were specifically marketed as prenatal supplements, the mean iodine content of prescription prenatal supplements was 150 ± 4.8 µg and for non-prescription prenatal supplements, it was 164 ± 6.7 ug [ 26 ]. As it is unlikely there has been a dramatic reduction in the amount of iodine included in dietary supplements containing at least some iodine, the lower median may be due to women reporting less frequent use of supplements.…”
Section: Discussionmentioning
confidence: 99%
“…In the less than daily and daily categories, the average daily dose was calculated as the sum of daily doses divided by number of days exposed and categorized as <400, 400 to <1,000, or ≥1,000 μg. When product name was unknown, FA dose was assumed to be 1,000 μg for prescription prenatals, 800 μg for nonprescription prenatals, and 400 μg for other nonprescription supplements, including FA‐only supplements (Saldanha et al, ). Mothers who did not report any supplements containing FA during this period were categorized as nonsupplementers (denoted as “None”) and constituted the reference category.…”
Section: Methodsmentioning
confidence: 99%
“…Prenatal vitamins typically contain higher amounts of FA, iron, and Vitamins B6 and B12 as compared to standard adult multivitamins, in order to meet the extra nutrient requirements of pregnancy [Schmidt et al, 2011]. However, there is also wide variability across formulations [Saldanha et al, 2017], and certain prenatal vitamins (such as many gummy vitamins) do not contain key nutrients like iron [WIC, 2018]. Studies examining prenatal vitamins in association with ASD have for the most part attributed observed protective associations to FA within the supplements, although the specificity of effects is difficult to determine.…”
Section: Prenatal Vitaminsmentioning
confidence: 99%